THE USE OF THE GEOGRAPHICAL INFORMATION SYSTEMS (G.I.S) IN THE GEOLOGICAL – MINERALOGICAL MAPPING OF THE PARANESTI AREA - Karageorgiou, M. M. D.; Karymbalis, E.; Karageorgiou, D.E. (Bulletin of the Geological Society of Greece, 2010)
The aim of this study is to emphasize the role of the Geographical Information Systems (GIS) technology for the collection, organization, analysis, modeling and presentation of data required for the geological and ore-deposits mapping. As a case study area the region of Paranesti in Northern Greece was selected as it is of exceptional geological and uranium mining interest. For the geological and ore deposit mapping of the study area data derived from analogue maps at various scales (topographical and geological) along with detailed field geological observations and measurements were organized in a spatial database with a common geographical coordinate system utilizing GIS technology. This procedure revealed the relation between the geographical distribution of uranium deposits and the geological structure of the area as well as the effect of the active tectonics.